2012
DOI: 10.1007/s00296-012-2556-4
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion body myositis associated with Sjögren’s syndrome

Abstract: Inclusion body myositis (IBM) belongs to the group of idiopathic inflammatory myopathies. It is a poorly understood disease, which affects skeletal muscles. IBM usually occurs as an isolated condition, but in some cases, it may be associated with another autoimmune disorder, Sjögren’s syndrome. We report a case of a 47-year-old woman with headaches, symptoms of trigeminal neuralgia, progressive weakness in muscles of the upper and lower extremities and symptoms of dry eyes and mouth. On admission, creatine kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Although inflammatory myopathy is rare in pSS, there are occasional reports of sIBM in patients with pSS . One study described 8 of 36 (22%) of patients with pSS and myalgia, who underwent muscle biopsy, showed histopathological features of IBM, although none had clinical features characteristic of this condition .…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammatory myopathy is rare in pSS, there are occasional reports of sIBM in patients with pSS . One study described 8 of 36 (22%) of patients with pSS and myalgia, who underwent muscle biopsy, showed histopathological features of IBM, although none had clinical features characteristic of this condition .…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analyses of the muscle tissue in cases of HIV-associated PM tend to show a significant decrease in endomysial CD4 + T lymphocytes, although these findings cannot be used to distinguish the condition from cases of non-HIV PM (17). Therefore, the muscle infiltrates observed in patients with SS consist of a mixture of B and T cells, with the proportions of CD4 + and CD8 + lymphocytes varying based on the individual case (18). In this manner, the molecular mechanisms underlying the development of myositis associated with SS and/or PM may have contributed to the onset of inflammatory myopathy noted in the present patient.…”
Section: Pm Coincides With Hiv Infectionmentioning
confidence: 65%
“…The generation of autoantibodies in patients suffering from HIV infection suggests polyclonal B cell function hyperactivity (18). In fact, light chain restriction without IgH rearrangement has been detected in reactive lymph nodes in patients with Castleman's disease, as well as autoimmune and viral disorders, such as herpes virus 6, Epstein-Barr virus (EBV) and HIV (32).…”
Section: Hiv and Autoimmune Antibodiesmentioning
confidence: 99%
“…Several patients with Sjögren syndrome have also been diagnosed with IBM [126], and in some of these cases, the muscle weakness was reported to respond to therapy [127,128]. It has further been suggested that IBM patients with…”
Section: Overlap Syndromes and Associated Diseasesmentioning
confidence: 99%
“…Sjögren syndrome may represent a subset of IBM [11,128], that may improve when treated early [127]. In a study of patients with rheumatoid arthritis, a sub-group of patients with myositis, either had a raise of erythrocyte sedimentation rate, not accounted for by synovitis, or of creatinine phosphate (CK), where muscle tissue of these patients was reported to exhibit de novo synthesis of rheumatoid factor and IgM [129], which was interpreted as evidence of a pathogenic overlap in these diseases.…”
Section: Overlap Syndromes and Associated Diseasesmentioning
confidence: 99%